Survey of dispensing rights among pharmacists and general practitioners (GPs) in state of Selangor / Nazif Salihin Ahmad Imran - Ahmad Imran, Nazif Salihin (2009)
Separation of dispensing and prescribing can be defined as a system that enables doctors and pharmacists to perform their distinct professional roles such that doctors examine and diagnose their patients and then decide upon relevant treatments and pharmacists dispense and administer the medicines according to the doctors' prescriptions. Currently, there is little survey done in Malaysia related to the dispensing separation between the pharmacists and the doctors. Pharmacists and doctors have different point of views regarding the dispensing right of pharmacist and the separation of dispensing and prescribing. Objectives of this study is to explore the opinion of pharmacists and general practitioners in state of Selangor regarding the separation of dispensing and prescribing in term of interest in the policy, expectation for the effect of the policy, to find why doctors oppose to the separation of prescribing and dispensing, and to access the level of knowledge of the separation policy among pharmacists and general practitioners. Mail surveys were given to the entire respondent that was selected randomly from two groups of respondents that were pharmacists and General Practitioners (GPs) from State of Selangor only. Out of total 500 respondents, only 78(15.6%) completed the questionnaire were returned to the researcher using envelope and stamp that have been provided. Mean score indicating interest in the separation policy, need of the policy and need for prohibiting pharmacists' prescribing were 2.74, 2.79 and 2.53 on a four-point scale respectively. Moreover, the overall level of expectation for the potential effects of the policy was high on pharmacists' side. In GPs view, they opposed the separation of dispensing and prescribing because they concerned about losing their professional rights and losing profits. For overall statements, it showed that pharmacists had higher knowledge about the policy of separation of prescribing and dispensing compared to the GPs. The result of study point to a need for the education initiatives that highlight the rules and regulations as well as the situation if the policy is going to be implemented.